Specificity protein 1 is pivotal in the skin’s antiviral response - Bin, Lianghua; Howell, Michael D.; Kim, Byung Eui; Streib, Joanne E.; Hall, Clifton F.; Leung, Donald Y.M. (Journal of allergy and clinical immunology, 2011)
Previous studies have found specificity protein (Sp) 1 transcription factor in the viral replication machinery and postulated that Sp1 was required for viral replication in host cells. We investigated the role of Sp1 in the skin’s antiviral responses from the perspective of host defense and its biological relevance in patients with atopic dermatitis and a history of eczema herpeticum (ADEH +). Small interfering RNA duplexes were used to knock down Sp1 in keratinocytes. The expression of vaccinia virus (VV), herpes simplex virus 1, and other genes were evaluated by real-time PCR, or combined with Western blot and immunohistofluorescence staining. A total of 106 human subjects participated in this study. Both VV and herpes simplex virus 1 replication were enhanced in Sp1 knocked-down keratinocytes. Sp1 gene expression was significantly decreased in ADEH + subjects compared with patients with atopic dermatitis without a history of eczema herpeticum and nonatopic subjects ( P < .0001) and inversely correlated with VV DNA copy number in human skin explants incubated with VV in vitro (partial correlation r = –0.256; P = .009). Gene profiling revealed that the antiviral genes, double-stranded RNA-dependent protein kinase (PKR) and 2’5’-oligoadenylate synthetase 2 (OAS2), were significantly downregulated in Sp1-silenced keratinocytes. Gene expression of PKR and OAS2 was also significantly decreased in skin biopsies from ADEH + subjects compared with patients with atopic dermatitis without a history of eczema herpeticum and nonatopic subjects. IFN-γ augmented the antiviral capacity of Sp1-silenced keratinocytes. Specificity protein 1 knockdown enhances viral replication in keratinocytes by downregulating gene expression of PKR and OAS2. Sp1 deficiency in ADEH + patients may contribute to their increased propensity to disseminated skin viral infections. IFN-γ augmentation may be a potential treatment for ADEH + patients.